Optimization of Selfnanoemulsifying Drug Delivery System (SNEDDS) Formulation of Ethil Acetate Fraction Soursop Leaf as Antioxidant - Dwi Saryanti; Iwan Setiawan (Indonesian Journal of Global Health Research, 2022)
Soursop leaves have acetogenin compounds that can be used to fight cancer in the presence of adenosine triphosphate (ATP) inhibition. Acetogenin is a long-chain fatty acid derivative (C23 or C34) which is very difficult to dissolve in water so that it will cause low oral bioavailability. The use of Selfnanoemulsifying Drug Delivery System (SNEDDS) as a drug delivery system can increase bioavailability and increase the solubility of a drug. Optimization of the use of VCO as the oil phase, tween 80 as surfactant and propylene glycol as co-surfactant in the SNEDDS formula using the Simplex Lattice Design method. The responses used in the optimization are % transmittance and emulsification time. Verification of the optimal SNEDDS formula obtained with one sample t-test. The optimal formula of SNEDDS ethyl acetate fraction of soursop leaves was tested for particle size with Partcle Size Analyzer, zeta potential with zeta sizer and antioxidant activity using ABTS. The optimal formula was obtained at the concentration of the components of VCO oil (0.56 ml), Surfactant (3.50 ml), and Propylene glycol (0.93 ml) with a desirability value of 0.769. The results of the verification of the optimal formula show that there is no significant difference between the prediction and the actual, which means that the Simplex Lattice Design method is valid and can describe the % transmittance response and emulsification time of SNEDDS ethyl acetate fraction of soursop leaves. The optimal formula for SNEDDS has an emulsification time of 53±1.527 seconds, transmittance value of % 96.3±0.360%. The particle size results obtained from the optimal formula were 13.83 nm ± 0.650, the polydispersity index was 0.143 ± 0.128. The zeta potential test results obtained were -0.23 mV ± 0.057. The optimal formula for the ethyl acetate fraction of soursop leaf SNEDDS has a very strong antioxidant activity with an IC50 value of 16.89 ppm.